The consequences of bad news writing towards sports journalism in Malaysia / Muhammad Izzat Syahmi Zulkaperi ... [et al.] - Zulkaperi, Muhammad Izzat Syahmi; Hamzah, Muhammad Hisyamuddin; Zainal, Ikhlas Fikry; Rashidi, Sarah Nur Alia; Norazman, Nurshahira Atiqah; Abd Razak, Ain Nadhirah (2019)
Good news writing 1s essential for every newspaper company either daily circulation newspaper or weekly. The project that the researchers researched on was based recent sport news headline that attacked and shamed national athlete. The purpose of this study is to find out the effect of bad news writing towards sports journalism. The method that the researchers applied in this case study is the qualitative method. The researchers conducted an in-depth interview with the public, media experts and retired journalists. The findings of the research showed that bad news writing in sports journalism can lead to the downfall of the sports news industry and can lose the public's trust in future news reports.